Family comes first a study of the impact of powerful families of the Philippines on economic growth - Agudo, Jemimah Rose N.; Menor, Steffanie Anne J.; Mendoza, Nimfa (Quezon City School of Economics, University of the Philippines Diliman, 2021)
Political dynasties have garnered a lot of attention in democratic countries in the whole world. Political dynasties are not only present in the Philippines but are also seen in Japan, India, Brazil, and the United States. Many studies have been done towards examining the effects that political dynasties bring which may either be positive, negative, or none at all. However, most literature available has been leaning towards the negative side of the spectrum towards their effect on the economy. There is a lack of literature specific in the Philippines, particularly towards economic performance. Two levels of analysis, particularly on the regional and provincial level, are performed to examine the effects of political dynasties in the Philippines. Using panel data fixed effects regression, the study finds strong evidence that political dynasties, particularly fat dynasties, have a negative effect on economic growth due to their enlarged scope both at the regional and provincial level despite having large income shares from the national government which positively affects economic growth.
Thesis (B.S. Economics) -- University of the Philippines Diliman
Keywords: Political culture -- Economic aspects -- Philippines; Political culture -- Philippines